Risperidone versus placebo for aggression following traumatic brain injury: a feasibility randomised controlled trial. Issue 9 (10th September 2020) - Deb, Shoumitro; Aimola, Lina; Leeson, Verity; Bodani, Mayur; Li, Lucia; Weaver, Tim; Sharp, David; Bassett, Paul; Crawford, Mike
Abstract : Objectives: To conduct a feasibility randomised controlled trial of risperidone for the treatment of aggression in adults with traumatic brain injury (TBI). Design: Multicentre, parallel design, placebo controlled (1:1 ratio) double-blind feasibility trial with an embedded process evaluation. No statistical comparison was performed between the two study groups. Setting: Four neuropsychiatric and neurology outpatient clinics in London and Kent, UK. Participants: Our aim was to recruit 50 patients with TBI over 18 months. Follow-up participants at 12 weeks using a battery of assessment scales to measure changes in aggressive behaviour and irritability (Modified Overt Aggression Scale (MOAS)-primary outcome, Irritability Questionnaire) as well as global functioning (Glasgow Outcome Scale-Extended, Clinical Global impression) and quality of life (EQ-5D-5L, SF-12), mental health (Hospital Anxiety and Depression Scale) and medication adverse effects (Udvalg for Kliniske Undersøgelser). Results: Six participants were randomised to the active arm of the trial and eight to the placebo arm over a 10-month period (28% of our target). Two participants withdrew because of adverse events. Twelve out of 14 (85.7%) patients completed a follow-up assessment at 12 weeks. At follow-up, the scores of all outcome measures improved in both groups. Placebo group showed numerically better score change according to the primary outcome MOAS. No severe adverse events were reported. The overall rate of adverse events remained low. Data from the process evaluation suggest that existence of specialised TBI follow-up clinics, availability of a dedicated database of TBI patients' clinical details, simple study procedures and regular support to participants would enhance recruitment and retention in the trial. Feedback from participants showed that once in the study, they did not find the trial procedure onerous. Conclusions: It was not feasible to conduct a successful randomised trial of risperidone versus placebo for post-TBI aggression using the methods we deployed in this study. It is not possible to draw any definitive conclusion about risperidone's efficacy from such a small trial. Trial registration number: ISRCTN30191436